The driving factors of Chinese outward foreign direct investmetn - Zhu, Pei (2012)
With the globalization of the economy, Chinese outward foreign direct investment (FDI) has increased dramatically in the last ten years. However, little attention has been attracted by researchers. The current study examines the driving forces of Chinese outward FDI and tests whether there are any differences in determining Chinese outward FDI between the developed regions and developing economies. The findings are based on the panel data set over the period 2003 to 2010. We find that Chinese outward FDI is driven by the strategic assets, openness to FDI and economic distance between home country (China) and host countries in all the economies. Also we find the evidences to support that there is distinctions in influencing Chinese outward FDI between developed economies and developing countries.